2023
DOI: 10.1108/md-08-2021-1050
|View full text |Cite
|
Sign up to set email alerts
|

Who discloses carbon information? The joint role of ownership and factor market distortion

Abstract: PurposeCorporations, as key contributors of greenhouse gas emissions, have been increasingly scrutinized by governments and stakeholders. Corporations have been asked to disclose their carbon-related information. This study investigates public corporate carbon disclosure, an imperative communication channel between firms.Design/methodology/approachThis study uses generalized estimation equation models with a longitudinal panel data of 311 listed firms in the China A-share stock index from 2010 to 2020. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
(113 reference statements)
1
4
0
Order By: Relevance
“…This study provides confirmation for the fourth hypothesis (H4) that SOEs in both Poland and in Hungary are less likely to set climate targets than the companies in which the government does not hold any stake. This result is in line with Chen et al [123] who found that, in China, private firms compared with state-owned enterprises (SOEs) are more willing to disclose carbon information. This result can be interpreted as an outcome of domestic governments focusing on minimising social costs related to energy transition and safeguarding energy security and affordability.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study provides confirmation for the fourth hypothesis (H4) that SOEs in both Poland and in Hungary are less likely to set climate targets than the companies in which the government does not hold any stake. This result is in line with Chen et al [123] who found that, in China, private firms compared with state-owned enterprises (SOEs) are more willing to disclose carbon information. This result can be interpreted as an outcome of domestic governments focusing on minimising social costs related to energy transition and safeguarding energy security and affordability.…”
Section: Discussionsupporting
confidence: 90%
“…However, Wu et al [124] analysed heavily polluting companies only, thus the companies in their sample could be driven to disclose carbon information because of their being under a tighter environmental scrutiny. Therefore, jointly with Chen et al, [123] presented results uncovering the negative effect of government ownership on corporate decarbonisation that can be observed in different institutional environments. Apparently, governments use state-owned enterprises to ensure the provision of essential services and promote social stability, while the goal of addressing market failures-negative pollution externalities-is compromised.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Fiorini et al [36] investigated the role of advanced information systems in facilitating firms' effective adoption of environmental management practices. Chen et al [37] showed that private firms demonstrate a greater willingness to disclose carbon emission information compared to state-owned enterprises. Furthermore, they found that firms operating in highly distorted factor markets are less inclined to disclose carbon information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ideally, manufacturing companies have to share information about material and water usage, carbon emissions, waste disposal methods and disclosure of other environmental issues for the concerned stakeholders (Liesen et al, 2017) as manufacturing companies are the major source of carbon emissions and other hazardous projects (Li et al, 2018). Different stakeholders want to know about the environmental condition of a company, but its company's discretion to inform them (Belal et al, 2015;Li et al, 2018) and private rms disclose more environmental information under legitimized pressure (Chen et al, 2023). There are many protection laws and agencies such as Pakistan Environmental Protection Act 1997, Pakistan Environmental Protection Council, Energy E ciency and Conservation Authority (ENERCON), Pakistan Forest Institute, National Council for Conservation of Wildlife, to safeguard, conserve and improve the environment through sustainable development measures (Zameenblog, 2023).…”
Section: Introductionmentioning
confidence: 99%